2020
DOI: 10.1111/dme.14379
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the diagnostic accuracy of the ankle–brachial pressure index for detecting peripheral arterial disease in people with diabetes: A systematic review and meta‐analysis

Abstract: Aim To systematically evaluate research investigating the accuracy of the ankle–brachial index (ABI) for diagnosing peripheral artery disease (PAD) in people with diabetes, as the accuracy is thought to be reduced in this cohort. Methods A database search of EBSCO Megafile Premier, Embase and The Cochrane Library was conducted to 28 February 2019. Prospective and retrospective investigations of the diagnostic accuracy of the ABI for PAD in people with diabetes using an imaging reference standard were eligible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(213 reference statements)
0
9
0
Order By: Relevance
“…Systolic and diastolic BP calculated from this mean, rather than measured directly, can be affected by stiffened arteries, as observed in older and diabetes patients. Therefore, in diabetes patients with a high proportion of stiffened arteries, ABI measurement has increased speci city, while sensitivity is compromised, compared to duplex Doppler ultrasound or digital subtract angiography in a meta-analysis 15 . Excluding diabetes patients from our study population improved the sensitivity of the oscillometric method.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic and diastolic BP calculated from this mean, rather than measured directly, can be affected by stiffened arteries, as observed in older and diabetes patients. Therefore, in diabetes patients with a high proportion of stiffened arteries, ABI measurement has increased speci city, while sensitivity is compromised, compared to duplex Doppler ultrasound or digital subtract angiography in a meta-analysis 15 . Excluding diabetes patients from our study population improved the sensitivity of the oscillometric method.…”
Section: Discussionmentioning
confidence: 99%
“…ABI has been considered a viable test to detect PAD, its diagnostic sensitivity ranges from 29 to 95% (average = 63%) and its specificity varies from 58 to 97 (average = 93%) [ 4 ]. In a recent meta-analysis, Chuter et al reported sensitivity and specificity of 60% and 87%, respectively, for ABI in patients with diabetes [ 8 ]. It is influenced by several factors, decreasing the test's sensitivity in renal failure and advanced stages or other disorders that result in vascular calcification (incompressible arteries) [ 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABI has been considered a viable test to detect PAD, its diagnostic sensitivity ranges from 29 to 95% (average = 63%) and its specificity varies from 58 to 97 (average = 93%) [ 4 ]. In a recent meta-analysis, Chuter et al reported sensitivity and specificity of 60% and 87%, respectively, for ABI in patients with diabetes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis in this issue of the journal highlights a low sensitivity, meaning peripheral arterial disease may not be diagnosed in people with diabetes when using the test. 5 This is a hugely exciting time for diabetes care. Rapid, accurate and precise measurement of multiple analytes and variables is possible with advanced data and bioinformatics tools to process those data and provide incredible insights into pathophysiology.…”
Section: Taking Measurementioning
confidence: 99%
“…The ankle‐brachial pressure index is non‐invasive, readily available, rapid, reproducible and widely understood. However, a meta‐analysis in this issue of the journal highlights a low sensitivity, meaning peripheral arterial disease may not be diagnosed in people with diabetes when using the test 5 …”
mentioning
confidence: 99%